Effect of Substrate Temperature on Structural and Optical Properties of Nanocrystalline CdTe Thin Films Deposited by Electron Beam Evaporation - M. Rigana Begam; N. Madhusudhana Rao; S. Kaleemulla; M. Shobana; N. Sai Krishna; M. Kuppan (Журнал нано- та електронної фізики)
Nanocrystalline Cadmium Telluride (CdTe) thin films were deposited onto glass substrates using electron beam evaporation technique. The effect of substrate temperature on the structural, morphological and optical properties of CdTe thin films has been investigated. All the CdTe films exhibited zinc blende structure with (111) preferential orientation. The crystallite size of the films increased from 35 nm to 116 nm with the increase of substrate temperature and the band gap of the films decreased from 2.87 eV to 2.05 eV with the increase of the crystallite size.